2012
DOI: 10.1021/ja301649k
|View full text |Cite
|
Sign up to set email alerts
|

Multistep Drug Intercalation: Molecular Dynamics and Free Energy Studies of the Binding of Daunomycin to DNA

Abstract: Atomic-scale molecular dynamics and free energy calculations in explicit aqueous solvent are used to study the complex mechanism by which a molecule can intercalate between successive base pairs of the DNA double helix. We have analyzed the intercalation pathway for the anticancer drug daunomycin using two different methods: metadynamics and umbrella sampling. The resulting free energy pathways are found to be consistent with one another and point, within an equilibrium free energy context, to a three-step pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
95
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(106 citation statements)
references
References 71 publications
10
95
0
Order By: Relevance
“…(1) Small molecule conformational sampling [73][74][75][76]; (2) Protein-folding [77][78][79] and large-scale protein conformational sampling [80][81][82][83]; (3) Protein-protein/peptide-peptide interactions [84][85][86][87][88][89][90][91][92]; (4) DNA conformational changes [93] and DNA-DNA interactions [94][95][96]; (5) Binding and association free-energies [97][98][99][100][101][102][103][104][105][106][107]; (6) Adsorption on and permeation through lipid bilayers [108][109][110][111][112][113][114][115][116][117] …”
Section: Umbrella Samplingmentioning
confidence: 99%
“…(1) Small molecule conformational sampling [73][74][75][76]; (2) Protein-folding [77][78][79] and large-scale protein conformational sampling [80][81][82][83]; (3) Protein-protein/peptide-peptide interactions [84][85][86][87][88][89][90][91][92]; (4) DNA conformational changes [93] and DNA-DNA interactions [94][95][96]; (5) Binding and association free-energies [97][98][99][100][101][102][103][104][105][106][107]; (6) Adsorption on and permeation through lipid bilayers [108][109][110][111][112][113][114][115][116][117] …”
Section: Umbrella Samplingmentioning
confidence: 99%
“…Also, the free energy profile is akin to what was observed for small molecule intercalation process. [25][26]30 However, unlike small molecule, intercalation of the AA in these DNA-AA systems results in the increase in free energy, due to hindrance from the backbone of AA. In case of the DNA-protein systems, both intercalation and deintercalation lead to an increase in the free energy indicating expectedly that the crystal structure is the most stable configuration.…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%
“…However, other studies showed that the recognizing ssDNA could bind ions, proteins, and drugs as well [148,149]. Upon binding, a negatively charged recognizing oligonucleotide is often conformationally transformed.…”
Section: Determination Of Proteinsmentioning
confidence: 99%